An Analysis of Factors Associated With Older Workers’ Employment Participation and Preferences in Australia - Noone, Jack; Knox, Angela; O’Loughlin, Kate; McNamara, Maria; Bohle, Philip; Mackey, Martin (Frontiers in Psychology, 2018)
Australian government and organizational age-management policies continue to target employment participation among older workers in light of an aging population. Typically, efforts to reduce early retirement among older workers have focused on well-established factors, including the promotion of worker health, reducing injury, supporting caregivers, reducing age discrimination and enhancing skill development. This research extends on the former approach by examining established factors along with important emerging factors, namely work-life balance, work centrality and person-job fit. Additionally, the research analyses the effects of gender and financial pressure on older workers’ employment participation and preferences. Logistic regression analysis of cross-sectional survey data involving 1,504 Australians aged 45 to 65, reveals that two established factors, physical health and caregiving, and all three emerging factors were associated with employment participation and preferences to be employed. However, important variations on the basis of gender and financial pressure were also identified. Caregiving was more strongly associated with the preference to remain employed for men (OR=.2.54, p<.01) than women (OR=1.03, ns) and person-job fit was more strongly associated with the preference to remain employed for women (OR=1.64, p<.001) than men (OR=.91, ns). Work-life conflict was more strongly associated with the preference to leave employment for those reporting limited financial pressure (OR=.60, p<.001) compared to those in poorer financial circumstances (OR=.87, ns). These findings suggest that organizational age management policies should focus on both established and emerging factors, particularly the provision of flexible working conditions and improving the psychosocial work environment. However, such efforts should carefully consider the different needs of men and women and those under varying levels of financial stress. With respect to government policy to promote employment participation, the findings support a stronger focus on improving physical and psychosocial work conditions rather than increasing the pension eligibility age. This may require further collaboration between government and employers.